Public opinion monitoring technologies: how the state uses data to make political decisions - Smailova, Aizhan; Kuzembayeva, Assiya; Utkelbay, Rysbek; Kukeyeva, Fatima; Baizakova, Kuralay (Frontiers in Political Science, 2025)
IntroductionThis study examines how the government of Kazakhstan uses national surveys and real-time sentiment analysis through social media monitoring to better understand public opinion and incorporate it into political decision-making. The increasing use of digital tools for governance creates new opportunities for responsiveness but also raises concerns about transparency and democratic accountability.MethodsA mixed-methods approach was employed, analyzing data from 2020 to 2024 using descriptive statistics and Pearson correlation to assess the relationship between technology adoption and policy responsiveness. In total, 72 policy decisions and 27 expert survey responses were examined to determine how digital technologies affect the timeliness and adaptability of state responses. The analysis covered 72 policy episodes with an average participation rate of 42 percent among relevant officials.ResultsThe findings indicate that traditional polling remains institutionally dominant; however, newer tools such as social media analytics and SMS polling are increasingly used for rapid feedback at the executive level. A strong positive relationship was identified between the use of sentiment analysis and the reduction of policy lag time, showing that digital technologies enhance governmental responsiveness.DiscussionThe study contributes to the body of knowledge on data-informed governance by empirically linking technological adoption with the timing of political action. While digital opinion tools improve policy responsiveness, they also present a double-edged challenge, serving both as instruments of administrative innovation and as potential tools of political control.